Measured ammonia emissions from tropical and subtropical pastures: A comparison with 2006 IPCC, 2019 Refinement to the 2006 IPCC, and EMEP/EEA (European Monitoring and Evaluation Programme and European Environmental Agency) inventory estimates - Arndt, Claudia; Misselbrook, Tom H.; Vega, Andrés; González-Quintero, Ricardo; Chavarro-Lobo, Johan A.; Mazzetto, Andre M.; Chadwick, Dave R. (American Dairy Science Association, Champaign, IL, EUA ; Elsevier, Ámsterdam, Países Bajos, 2020)
Agriculture is the largest source of ammonia (NH3) emissions. As NH3 is an indirect greenhouse gas, NH3 measurements are crucial to improving greenhouse gas emission inventory estimates. Moreover, NH3 emissions have wider implications for environmental and human health. Only a few studies have measured NH3 emissions from pastures in the tropics and subtropics and none has compared emissions to inventory estimates. The objectives of this study were to (1) measure NH3 emissions from dairy pastures in tropical and subtropical regions; (2) calculate NH3 emissions factors (EF) for each campaign; and (3) compare measured EF with those based on the 2006 Intergovernmental Panel on Climate Change (IPCC) Tier 1, 2019 Refinement to the 2006 IPCC Tier 1, and the European Monitoring and Evaluation Programme/European Environmental Agency (EMPE/EEA) Tier 2 inventory estimates. Pasture NH3 emissions were measured on 3 dairy farms in Costa Rica. On each dairy, NH3 emissions were measured twice during the wet season and once during the dry season using a micrometeorological integrated horizontal-flux mass-balance method. Emissions were measured from excreta (dung and urine) deposited by grazing cattle and the subsequent application of organic (slurry) or synthetic fertilizer (ammonium nitrate or urea). Measured EF for all campaigns [from grazing cattle excreta and any subsequent slurry or fertilizer application; 4.9 ± 0.9% of applied nitrogen (mean ± SE)] were similar to those of the EMEP/EEA Tier 2 approach (6.1 ± 0.9%; mean ± SE) and 4 times lower than 2006 IPCC and 2019 Refinement to 2006 IPCC Tier 1 default estimates (17.7 ± 1.4 and 18.2 ± 0.9%, respectively; mean ± SE). Measured EF for excreta deposited on pasture and excreta both deposited on pasture and slurry application [3.9 ± 2.1 and 4.2 ± 2.1% (mean ± 95% CI), respectively] were 5 times lower than default EF assumed by 2006 IPCC and 2019 Refinement to 2006 IPCC methodology (both 20 and 21%, respectively), whereas EMEP/EAA estimates were similar [6.0 and 4.6 ± 0.3% (mean ± 95% CI), respectively]. This suggests an overestimation of EF from excreta deposited on pasture and slurry applications in tropical and subtropical regions by IPCC methodologies. Furthermore, rainfall, which is not included as a parameter in the current EMEP/EEA Tier 2 methodology, appeared to reduce NH3 emissions, suggesting that accounting for this in the inventory methodologies could improve inventory estimates.